Breast cancer chemoprevention - Ivana Sestak; Jack Cuzick (Frontiers Media S.A., 2011)
Trials with tamoxifen have clearly shown that the risk of developing oestrogen receptor positive breast cancer can be reduced by at least 50% with prophylactic agents. The current challenge is to find new agents which achieve this or better efficacy, but with fewer side effects. Recent results indicate that the SERM raloxifene has similar efficacy to tamoxifen, but leads to fewer endometrial cancers, gynecological symptoms, and thromboembolic events. Results for contralateral tumors in adjuvant trials suggest that aromatase inhibitors may be able to prevent up to 70%-80% of ER-positive breast cancers, and this is currently being investigated in two large prevention trials, one using anastrozole (IBIS-II) and the other exemestane (MAP.3). New agents are needed for receptor negative breast cancer and several possibilities are currently under investigation.